PENILAIAN KINERJA KEUANGAN KOPERASI SIMPAN PINJAM BUNGA BARU - RADEN S B SUHARTO (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2015)
The purpose of this study was to determine the Financial Performance Credit Unions New Interest inNamosain Kupang in The analysis technique used is the Quantitative Descriptive describe and explain thecircumstances Cooperative performance in 2011 and 2012 and did an explanation of the results. Analysistools used are financial ratios to approach PEARLS. The study of cooperative performance in 2011 ofProtection components shows the results of 64.74%, this value into the category of good performance,efective Financial Structure 24.27%, this value into the category of performance Less Good, QualityAsets 123.63%, The values in the category of very good performance, rate of return on cost 51.73%where the value is in the category of performance is quite good, Liquidity 41.92%%, this value into thecategory of performance is quite good, Signs of Growth 39.92 % where the value is in the category of lessgood performance. Thus, the performance of the Cooperative New Interest in 2011 was in the category ofreasonably well with a value of 57.70%. The study of cooperative performance in 2011 shows that theProtection shows the results of 54.31%, this value into the category of performance is quite good, efectiveFinancial Structure 25.98%, this value into the category of performance Less Good, Quality Asets157.18% , this value into the category of very good performance, rate of return on cost of 96.84% wherethe value is in the category of very good performance, Liquidity 21.64%, this value into the category ofless good performance, Signs of Growth 33.30 %, the value is in the category of performance than Good.Thus, the performance of the Cooperative New Interest in the year 2012 is included in the GOODcategory with a value of 64.85%, this means an increase of cooperative performance is good enough to begood Cooperative Performance New Interest in 2011 was in the category Good Enough for a value of57.70%, and the performance of cooperative New Interest in 2012 in the category of a good with a valueof 64.85%. The results showed Protection for 2011 and 2012 in both categories, it is advisable to beincreased next year by increasing reserve funds and reduce the risk of total loans negligence. The resultsshowed Rate of return on cost for 2011 and 2012 in the category No Good, it is suggested that thiscondition can be corrected in the next year, by way of increasing the value of the return on investment inloans.